Expanding the scope of Technology Assessment (TA): a critical narration from the Iranian digital technologies case - Narges Naraghi; Soroush Ghazinoori (Journal of Responsible Innovation)
Technology Assessment (TA) theories and methods have taken the global North as their predominant context; however, they are being adapted increasingly in the South. Against this backdrop, elaborating on the theoretical potential of TA, this research tries to critically reflect on the shortcomings of Southern voices in the mainstream TA literature. Gathered through extensive expert interviews and mapped into the novel ontological matrix of TA, our data is interpreted to answer the research question: why and how is TA perceived differently in the Iranian context than in the mainstream TA literature? Candidate variables to answer this question are power relations and ideological governance of the TA playground; political, hegemonic, and executive power of the assessor; and the agency of the assessee and the society in counter-defining each other. Acknowledging these variables could lead to realizing TA's potential, expanding its perceptions' scope, and facilitating its implementations in non-mainstream contexts, like Iran.